Structure and gas-sensing characteristics of undoped tin oxide thin films fabricated by ion-assisted deposition - Song, SK; Cho, JS; Choi, WK; Jung, HJ; Choi, DS; Lee, JY; Baik, HK; Koh, SK (ELSEVIER SCIENCE SA, 1998)
Undoped SnOx thin films were deposited by a reactive ion assisted deposition technique at various ion beam potential (V-1) onto amorphous SiO2/Si substrates at room temperature. Crystalline structures of the films were investigated in terms of grain size, composition ratio, porosity and peak area percent of adsorbed oxygen. Sensitivities for propane (C3H8), methane (CH4) and hydrogen (H-2) gas in SnOx gas sensor devices were characterized at the substrate temperatures of 100-500 degrees C. The gas sensitivities depend on the grain size rather than the porosity. It is also proportioned to the amounts of adsorbed oxygen at room temperature by SPS analysis. (C) 1998 Elsevier Science S.A. All rights reserved.